Gagasan Penyederhanaan Jumlah Partai Politik Dihubungkan Dengan Sistem Pemerintahan Republik Indonesia - Mexsasai Indra (Fakultas Hukum Universitas Riau, 2011)
Political reforms in 1998 which was followed by a free and democratic elections in 1999, has a fairly fundamental change relationship patterns that characterized the President and the Parliament many political parties that play a role in the constitutional structure. Because it came back the idea of ​​simplification is a political party. efforts to simplify the number of political parties is a must in order to support an effective presidential system of government, while the effort to do that is by simplifying the number of political parties naturally through the electoral threshold, tighten the terms of the establishment of political parties dismaping it is also the reality that there is currently a clear need for regulation of the coalition system.